The effects of curculigo latifolia dry and ethanolic extracts on sperm quality of mice mus musculus / Faridahanim Mohd Jaafar - Mohd Jaafar, Faridahanim; Zainal, Farah Shahirah; Ahmat, Norizan; Daud, Dzulsuhaimi; Hashim, Nooraain (Universiti Teknologi MARA Cawangan Pulau Pinang, 2017)
Several Curculigo species have been reported to be widely used for the treatment of impotence and act as aphrodisiac. However, the effect of Curculigo latifolia Dryand on sperm quality, defined as the measurable parameters of the sperm sample which may determine its fertilising capacity, has not been completely explored. The objective of this study was to determine and compare the effects of the leaf and root extracts of Curculigo latifolia on the sperm quality of mice Mus musculus. Three groups of male mice were used in this study; the control group (Group 1) was forced-fed with saline solution, Group 2 with 500 mg/kg b wt of the root extract of C. latifolia and Group 3 with 500 mg/kg b wt of the leaf extract of the plant. The treatments were conducted for a duration of 14 days. The results of this study gave no significant difference in the weekly body weight and sperm morphology of the mice. Mice fed with the root extract showed a greater increase in sperm motility (75.33±2.60%) compared to Group 3 (74.00±5.00%) and Group 1 (64.33±2.73%). Meanwhile, mice fed with the leaf extract showed a higher sperm count (62.33±4.33 mill/ml) and sperm viability (28.00±4.04%) compared to Group 2 (58.67±4.10 mill/ml and 27.67±5.55%, respectively) and Group 1 (40.33±3.18 mill/ml and 23.33±2.96%, respectively). In conclusion, the leaf and root extracts of Curculigo latifolia appeared to have positive effects on sperm quality parameters which are linked to male fertility.